Hubungan antara Kepribadian Ekstraversi dan Kesepian dengan Kecenderungan Nomophobia pada Remaja - Ciptadi, Wenny Acnashinta; Selviana, Selviana (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
This study aims to examine the relationship between extraversion personality and loneliness with the tendency of nomophobia. The research respondents were teenagers in class XI and XII in SMA Annajah totaling 160 people using simple random sampling. Data analysis uses correlation bivariate which shows that there is a positive and significant relationship between personality extraversion and the tendency of nomophobia, r = 0.336 and p 0.000 <0.05. There is a positive and significant relationship between loneliness and the tendency of nomophobia with r = 0.019 with p 0.01 <0.05. Based on multivariate correlation analysis shows that there is a positive and significant relationship between extraversion and loneliness with the tendency of nomophobia with R = 0.344 and p = 0.000 <0.05 with the effective contribution of extraversion and loneliness to the tendency of nomophobia by 11.8%. The rest is contributed by other factors not examined.